TAX SIMPLIFICATION. - Bachrach, Michael D. (The Accounting Review, 1945)
Abstract The article presents information on tax simplification. During the past few months, numerous committees representing various business and professional organizations have been working at the task of suggesting ways of "simplifying" the Federal income tax law. Their purpose is to make recommendations to Congress which, if adopted, will presumably result in a plainly written, easily understandable statute, supplemented (it is hoped) by equally clear regulations. The announced objectives of the tax planners are threefold: (1) simplification; (2) elimination of "inequities" and (3) encouragement of "risk capital." After studying the recommendations, Congress may proceed in one of two ways to bring about the desired reforms: it may repeal the existing Internal Revenue Code and enact a brand-new law, or it may retain the Code in its present form and make such changes as appear to be in order. Despite the apparent advantages of making a clean sweep and starting over, it would probably be impractical to discard the accumulated body of law and precedent; hence "simplification" will likely be accomplished by revising the present Code. To help bring about the maximum "simplification," it is suggested that certain sections be entirely removed from the Code.